Fishing for NUMTs: exploring mitochondrial insertions in fish (2025)
NUMTs can be defined as fragments of mitochondrial DNA that have been integrated into the nuclear genome through evolutionary processes. Once NUMTs are inserted they can potentially disrupt protein-coding genes, leading to disease or integrate successfully into the genome and change the phenotype of the organisms and thus its survival. NUMTs have been used to define phylogenetic outgroups and elucidate mtDNA evolution. While NUMTs have been extensively studied in vertebrates, their distribution, frequency, and evolutionary significance in fish remain largely unexplored. In this study, a novel bioinformatics pipeline using LAST is suggested as a potential method to identify NUMTs in the genomes of ten fish species. A total of 583 NUMTs were detected, with significant variation in NUMT content across species. Our findings suggest that genome size is not a strong predictor of NUMT abundance in fish. Additionally, an analysis of ancient NUMTs revealed that only Elasmobranchii (sharks and rays) retained conserved NUMT sequences, likely due to their slow genomic evolutionary rates. No ancient NUMTs were identified in Actinopterygii, possibly due to their high evolutionary divergence. These results provide new insights into the distribution and evolutionary history of NUMTs in fish and highlight the potential of NUMTs as markers for studying genome evolution. Further research on NUMTs in closely related fish taxa and improvements in the workflow could refine our understanding of their functional and evolutionary implications, particularly in species with highly conserved genomes.